Antibiotic resistance of Vibrio parahaemolyticus isolated from pond-reared Litopenaeus vannamei marketed in Natal, Brazil - Ligia Maria Rodrigues de Melo (Brazilian Journal of Microbiology, 2011)
Ten out of fifty fresh and refrigerated samples of shrimp (Litopenaeus vannamei) collected from retailers in Natal (Rio Grande do Norte, Northeastern Brazil) tested positive for Vibrio parahaemolyticus. The Kanagawa test and multiplex PCR assays were used to detect TDH and TRH hemolysins and the tdh, trh and tlh genes, respectively. All strains were Kanagawa-negative and tlh-positive. Antibiotic susceptibility testing was done for seven antibiotics by the agar diffusion technique. Five strains (50%) presented multiple antibiotic resistance to ampicillin (90%) and amikacin (60%), while two strains (20%) displayed intermediate-level resistance to amikacin. All strains were sensitive to chloramphenicol. Intermediate-level susceptibility and/or resistance to other antibiotics ranged from 10 to 90%, with emphasis on the observed growing intermediate-level resistance to ciprofloxacin. Half our isolates yielded a multiple antibiotic resistance index above 0.2 (range: 0.14-0.29), indicating a considerable risk of propagation of antibiotic resistance throughout the food chain.